Discourse and text in translation - Demetskaya, V. V. (Cognition, Communication, Discourse, 2018)
This article focuses on the problems of text and discourse in connection with the theory of translation. The concept of discourse, its vertical and horizontal varieties, pragmatic features of texts of different genres are specified. It is proved that cultural asymmetry stipulates distinctions in the paradigm of texts and dominant discourse functions. Their preservation in translation stipulates adequate authentication and interpretation of the type of discourse.